2013
DOI: 10.1111/bjd.12563
|View full text |Cite
|
Sign up to set email alerts
|

Infants' Dermatitis Quality of Life Index: a decade of experience of validation and clinical application

Abstract: The Infants' Dermatitis Quality of Life Index (IDQoL) is a questionnaire completed by parents to assess the impact of atopic dermatitis on the quality of life of infants aged 0-3 years. The aim was to review all clinical and psychometric data on the use of the IDQoL from its inception in 2001 until November 2012, to serve as a single reference source. A literature search was carried out using Medline, PubMed, EBSCOhost, Science Direct and Google Scholar. Articles and abstracts that described the clinical use o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 48 publications
3
34
0
3
Order By: Relevance
“…Only a few studies have examined the correlation between the Objective SCORAD and the QoL in children <4 years old using the IDQoL, and the conclusions of those studies are conflicting [25,26,27,28,38,39]. We found that the subjective QoL scores of the children were positively correlated with the objective severity assessments of AD when using the Objective SCORAD, with a significant and good correlation in both the older and the younger age group.…”
Section: Discussionmentioning
confidence: 72%
“…Only a few studies have examined the correlation between the Objective SCORAD and the QoL in children <4 years old using the IDQoL, and the conclusions of those studies are conflicting [25,26,27,28,38,39]. We found that the subjective QoL scores of the children were positively correlated with the objective severity assessments of AD when using the Objective SCORAD, with a significant and good correlation in both the older and the younger age group.…”
Section: Discussionmentioning
confidence: 72%
“…It is helpful, if QoL instrument developers summarize and report on the later published experience of their use, although this seldom happens. In reviews parallel to the ‘PostMarketing’ surveys of new therapies, we have reported on 10‐20 years experience of the PDI, DLQI, CDLQI, IDQoL and DFI . These summaries bring together many aspects of validation of these measures that would otherwise remain scattered and unidentified in the literature.…”
Section: Practical Management Of Qol Toolsmentioning
confidence: 99%
“…A simple scheme is shown in Table 1,[1] but other scores include physician measures of severity such as SCORAD, EASI, and SASSAD[2] and patient measures such as Patient Orientated Eczema Measure. [3] Quality of life tools include CDLQI,[4] IDQOL,[5] and FDLQI. [6]…”
Section: Assessmentmentioning
confidence: 99%